Back-Effluerage Massage (BEM) terhadap Nyeri dan Tekanan Darah Ibu Bersalin Kala I - Halimatussakdiah Halimatussakdiah (Jurnal Kesehatan, 2017)
Pain is unpleasant emotional and neurological experience, one feels that a treatment indispensable, labor pain causes mother to worry that they will not be able to pass through the birth process. This study were to determine the effect of Back-Effleurage Massage (BEM) to changes in pain and vital sign, before and after intervention of BEM in Women who childbirth at Stage I. This study was a quasi-experiment. Populationwere all of mother who childbirth stage I, active phase, in delivery room of Aceh Government Public Hospital. 30 mothers were taken with accidental sampling. The instruments were Numeric Rating Scale (NRS) and sphygmomanometer. Data were collected through guided interviews and analyzed by univariate and Bivariate with paired t-test. The result indicated that BEM can reduce pain intensity p=0,000, change systolic blood pressure p=0,000, alter blood pressure diastolic, at the value ofp =0.0016. The study concludes that BEM affects pain and vital sign of Women who childbirth at Stage I.